Application of Logistic Regression Model to Assess Quality Development in Organizations in Central Pomerania Region - Marcin OLKIEWICZ; Joanna Alicja DYCZKOWSKA (Communications of International Proceedings, 2023)
The article focuses on the area of assessing quality development in organizations within standardized management systems. The aim of the research was to identify and assess the effectiveness of standardized management systems in organizations in Central Pomerania using a logistic regression model. The source of the data were the results of two surveys conducted among 1623 business entities in the Central Pomeranian region. The obtained results prove that the standardized management systems operating in organizations are very effective, which increases the likelihood of maintaining the continuity of quality improvement activities in all areas of activity of the surveyed organizations.
Keywords: Efficiency model; logistic regression; shaping quality; management systems